THE CHARACTERISTIC ELECTRONIC-STRUCTURE NEEDED FOR HIGH-TEMPERATURE SUPERCONDUCTIVITY - REPLY - Pyper, N; Edwards, P (1991)
It is shown that the magnon mechanism proposed by Goddard and co-workers to explain high-temperature superconductivity in oxidized cuprates can also account for such superconductivity in both oxidized barium bismuthate and the electron superconductors based on neodynium cuprate. The specific and characteristic electronic structure required for the operation of the magnon mechanism naturally accounts for why only a small number of basic types of high-temperature superconductors are currently known. This mechanism can readily explain the effects of doping cuprate superconductors with both magnetic and non-magnetic ions. © 1991.